The Shoah Simulacrum: postmemory and spectral homecoming in Maxim Biller’s novella “Harlem Holocaust” - Veronika Köver (University of Edinburgh, 2008)
In the context of the current German memory discourse, the age-old question of the interplay of remembrance and effacement has been revived. This article proposes to shed light on some of its ramifications through the prism of Maxim Biller’s novella Harlem Holocaust. Biller, born 1960 in Prague, is a German-Jewish short-story writer, novelist and newspaper columnist. Initially known for his incisive articles in the quasi legendary Tempo magazine and now for his satirical column “Moralische Geschichten” in the Frankfurter Allgemeine Sonntagszeitung, Biller writes on socio-political, cultural and personal issues, touching on German reunification, American literature, latent anti-semitism and convoluted love relationships. His novels and short stories are highly. A close reading of his novella Harlem Holocaust in the light of Marianne Hirsch’s notion of postmemory and Jean Baudrillard’s concept of the simulacrum facilitates the comprehension of how the German discourse on memory has slowly been hollowed out, persisting nowadays as pure form engaged in a spectral homecoming. Indeed, old memories – distorted through the manipulation as much as through the natural erosion of the past – are returning to haunt the present, oblivious that they are only spectres.